HSC70 and HSP90 chaperones perform complementary roles in translocation of the cholera toxin A1 subunit from the endoplasmic reticulum to the cytosol - Burress, Helen (J Biol Chem, 2019)
Cholera toxin (CT) travels by vesicle carriers from the cell surface to the endoplasmic reticulum (ER) where the catalytic A1 subunit of CT (CTA1) dissociates from the rest of the toxin, unfolds, and moves through a membrane-spanning translocon pore to reach the cytosol. Heat shock protein 90 (HSP90) binds to the N-terminal region of CTA1 and facilitates its ER-to-cytosol export by refolding the toxin as it emerges at the cytosolic face of the ER membrane. HSP90 also refolds some endogenous cytosolic proteins as part of a foldosome complex containing heat shock cognate 71-kDa protein (HSC70) and the HSC70/HSP90-organizing protein (HOP) linker that anchors HSP90 to HSC70. We accordingly predicted that HSC70 and HOP also function in CTA1 translocation. Inactivation of HSC70 by drug treatment disrupted CTA1 translocation to the cytosol and generated a toxin-resistant phenotype. In contrast, the depletion of HOP did not disrupt CT activity against cultured cells. HSC70 and HSP90 could bind independently to disordered CTA1, even in the absence of HOP. This indicated HSP90 and HSC70 recognize distinct regions of CTA1, which was confirmed by the identification of a YYIYVI-binding motif for HSC70 that spans residues 83–88 of the 192-amino acid CTA1 polypeptide. Refolding of disordered CTA1 occurred in the presence of HSC70 alone, indicating that HSC70 and HSP90 can each independently refold CTA1. Our work suggests a novel translocation mechanism in which sequential interactions with HSP90 and HSC70 drive the N- to C-terminal extraction of CTA1 from the ER.